Tailoring the size and magnetic property of biogenic silver nanoparticles - Shah Mohammad , Rayhan; Kabir, Md Faysal; j., Ferdousy; A. K. M. , Atique Ullah; Rahman , Rahman (Malaysian NANO-An International Journal, 2022)
By exploring biological sources, the area of nanotechnology is currently thriving and offers a fresh method. Plant extract-mediated green nanomaterial synthesis has gained appeal as a result of its cost-effectiveness and environmentally beneficial characteristics. In this study, Ag NPs were successfully synthesized from reducing Ag+ ions using Mangifera indica leaf extracts as a source of reducing and capping agents. Several different microscopic and spectroscopic approaches were used in order to characterize the produced Ag NPs. Analyses using XRD and SEM have been carried out to look into the morphology of the generated Ag NPs. The (XRD) pattern peaks are associated with the metallic silver in the (FCC) shape. Silver nanoparticles average grain size is in the 10–100 nm range for all concentrations of AgNO3. The shape of the produced silver nanoparticles was determined to be round and spherical by (SEM), and their total size was determined to be between 50 and 100 nm. Analysis using EDX spectroscopy also demonstrated the production of silver and the presence of components that performed the function of a capping agent. (FT-IR) spectra were performed in order to determine the organic groups like carbonyl, hydroxyl, amine, and protein molecules. Analysis using (FT-IR) spectroscopy publicized the presence of flavonoids, polyphenols, and amide groups, all of which are candidates for being responsible for the environmentally friendly creation of silver nanoparticles. From (VSM) analysis, the biosynthesized Ag NPs were weak ferromagnetic in nature, which would be a potential research arena, especially for device application and medical equipment construction using these magnetic crystalline AgNPs. Keywords: Ag NPs, synthesized, X-ray Diffraction, TGA, magnetization